2006
DOI: 10.1016/j.trstmh.2006.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of multidrug-resistant Shigella dysenteriae type 1 causing dysentery outbreaks in Central African Republic, 2003–2004

Abstract: Shigella dysenteriae type 1 (Sd1) represents a particular threat in developing countries because of the severity of the infection and its epidemic potential. Antimicrobial susceptibility testing and molecular subtyping by pulsed-field gel electrophoresis (PFGE) and plasmid profiling (PP) of Sd1 isolates collected during two dysentery outbreaks (2013 and 445 cases of bloody diarrhoea) in Central African Republic (CAR) during the period 2003-2004 were reported. Eleven Sd1 comparison strains (CS) acquired by trav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…In 2003, 2004 and 2005, Shigella dysenteriae was responsible for two epidemic episodes in CAR [4,11], but in our hospital survey, Shigella flexineri was the only species isolated. Thus, Shigella flexineri is apparently endemic to the population as described in Tunisia, while Shigella dysenteriae would be mainly associated with outbreaks [3].…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…In 2003, 2004 and 2005, Shigella dysenteriae was responsible for two epidemic episodes in CAR [4,11], but in our hospital survey, Shigella flexineri was the only species isolated. Thus, Shigella flexineri is apparently endemic to the population as described in Tunisia, while Shigella dysenteriae would be mainly associated with outbreaks [3].…”
Section: Discussionmentioning
confidence: 65%
“…Shigella flexneri is the leading cause of shigellosis, particularly in the poor populations [3]. Shigellosis is endemic in Central African Republic (CAR), where an outbreak of Shigella dysenteriae type 1 was recently reported [4]. The present study was undertaken to determine the prevalence and the antimicrobial susceptibility patterns of Shigella serotypes in children hospitalized for diarrhoea in a paediatric unit in Bangui, CAR.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports described the large outbreak of S. dysenteriae dysentery among Rwandese refugees after the 1994 civil war [36,40,42,52], reporting similar patterns of multidrug resistance including nalidixic acid and trimethoprim, leaving the newer fluoroquinolones as a treatment option. Bercion et al [38] and Cunin et al [44] described similar outbreaks in CAR and Cameroon, respectively. Even outside the epidemic context, the prevalence of multidrug-resistant strains was found to be >50% in recent reports from Kinshasa (DRC) [49] and Bangui (CAR) [53].…”
Section: Gram-negative Bacteriamentioning
confidence: 86%
“…Shigella spp. [16,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] Eighteen studies were found, mainly from rural DRC (12/18; 66.7%) and published between 1955 and 2006. Two-thirds reported on outbreak investigations, and Shigella dysenteriae type 1 was the predominant serotype (15/18 studies).…”
Section: Gram-negative Bacteriamentioning
confidence: 99%
“…In the last decade, large Sh. dysenteriae type I outbreaks have been documented from the Central African Republic (2 outbreaks) [150], Cameroon [151], Sierria Leone [152], Zimbabwe [153], South Africa [154], and Kenya [155], in addition to numerous sporadic reports.…”
Section: Enteroinvasive E Coli and Shigellamentioning
confidence: 99%